Phase mixing and separation in 2D supramolecular networks - Allen, Alexander (2021)
The study of molecular assemblies through the use of SPM is well documented. This thesis examines assemblies of bi-isonicotinic acid (formally 4,4-dicarboxy-2,2-bipyridine), which forms assemblies that appear to be hydrogen bonded. The interesting element inspiring the study of this molecule is its surface-induced chirality, which restricts certain bonding configurations and orientations.